COLLABORATIVE LEARNING TO IMPROVE READING COMPREHENSION - Fitriyeni Fitriyeni; Tri Widyastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Collaborative learning is one of the method of teaching and learning that motivate the students to work in group and discuss their learning with their pairs so that the students have to share their knowledge and opinions. It gives the students opportunity to teach each other and collaborate their learning simultanously. Reading becomes more enjoyable for the students due to their collaborativeness in trying to understand the passage being read and comprehend their reading. The process of learning also makes the students aware of their strength and weaknesses. Therefore, the research is conducted to know the effect of both variables. The Research methodology used is descriptive quantitative study using 80 students as the sample which is chosen randomly. Data was collected through pre test and post test in the form of multiple choice test to the samples. Data analysis uses descriptive statistics. The research result shows that there is a significant effect of collaborative learning and the students’s reading comprehension. It means that the implementation of collaborative learning method has influenced the students’ comprehending of the reading passage better. The students completely engage in their learning and motivate each other to understand the reading and answering the tasks. Teachers also have good influenced as facilitators to help the students in building relationship in their groups and encourage them to give and respon to their pairs’ opinions